2019
DOI: 10.1590/1980-5918.032.ao38
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level and associated factors: an epidemiological study with elderly

Abstract: Introduction: This study is relevant insofar since it provides information on the elements that interfere in the level of physical activity of the elderly that attend the Fitness zone. Objective: Identifying the level of physical activity and its associated factors related to the elderly who usually go to third age fitness centers in Maringá/PR. Method: A cross-sectional study was carried out with 970 elderly users of the Fitness zone of the municipality of Maringá, state of Paraná, Brazil. A sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
4
Order By: Relevance
“…Regular physical activity is important in maintaining the health of older people, which should be increasingly encouraged in long-lived adults. Oliveira et al [27] found a significant association between PAL and perceived health (p = 0.037), number of drugs used (p = 0.008) and the history of near falls among older individuals in the last semester (p = 0.038), demonstrating that physical activity was important in reducing actions associated with health-related variables.…”
Section: Discussionmentioning
confidence: 98%
“…Regular physical activity is important in maintaining the health of older people, which should be increasingly encouraged in long-lived adults. Oliveira et al [27] found a significant association between PAL and perceived health (p = 0.037), number of drugs used (p = 0.008) and the history of near falls among older individuals in the last semester (p = 0.038), demonstrating that physical activity was important in reducing actions associated with health-related variables.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to vegetarian types and BMI, sociodemographic variables and health conditions have been suggested to be associated with physical activity levels [ 45 , 46 ]. However, in the present study, we did not find significant differences in sociodemographic variables and comorbidities (except for osteoarthritis) between vegetarian and nonvegetarian women.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Dunn index suggests categorization into four groups, which is already proposed in the literature by Matsudo et al [ 26 ], which recommends classifying the investigated as sedentary, insufficiently active, active and very active. It should be noted that other studies carried out by Brazilian researchers have already done the clustering into two groups [ 59 – 63 ]. In it, was possible to observe the reclustering between the sedentary/insufficiently active and active/very active categories.…”
Section: Discussionmentioning
confidence: 99%